Dendrobium officinale polysaccharides protected against ethanol-induced acute liver injury in vivo and in vitro via the TLR4/NF-κB signaling pathway. (June 2020) - Yang, Ke; Zhan, Lianghui; Lu, Tingting; Zhou, Cong; Chen, Xue; Dong, Yingjie; Lv, Guiyuan; Chen, Suhong
Graphical abstract: Highlights: DOP showed the protective effect of acute alcoholic liver injury. DOP inhibited alcohol-induced inflammatory responses in vivo and vitro . DOP inhibited activation of TLR4/NF-κB signaling pathway. Abstract: Alcohol-induced liver injury is characterized by strong inflammation. Polysaccharides separated from herbs can prevent ethanol-induced liver injury. Dendrobium officinale Kimura et Migo leaves ( D. officinale ) are a new food resource that contains a certain amount of polysaccharide. However, the hepatoprotective effects and the potential mechanisms of D. officinale polysaccharide (DOP) remain unknown. Thus, this study aimed to assess the hepatoprotective effects and potential mechanism in vivo and in vitro of DOP. Male Sprague–Dawley rats were used to establish alcohol-induced liver injury models through the oral gavage of absolute alcohol (5 mL/kg) after the oral administration of DOP (400 and 100 mg/kg) for 30 days. Hematoxylin–eosin staining was used for the histological assessments of hepatocyte degeneration, and the AST and ALT levels in the serum and liver tissue were measured. The inflammatory markers were evaluated using ELISA and immunohistochemistry. The potential mechanism of DOP in alcohol-induced liver cell (LO2 ) injury in vitro was further identified. Results showed that DOP clearly decreased the AST in the serum and hepatic tissue, obviously reduced the production of inflammatory cytokines (such as IL-1β, IL-6, and TNF-α), and can successfully inhibit NF-κB phosphorylation in vivo. In vitro experiments indicated that DOP increased the LO2 cell viability; prevented LDH release prominently; reduced the secretion of IL-1β, IL-6, and TNF-α; and reversed the expression of IL-1β, IL-6, TNF-α, caspase 1, NLRP3, p-NF-κB, and TLR4. Overall, DOP can alleviate ethanol-induced acute liver injury via the TLR4/NF-κB signaling pathway.